BUSINESS DEVELOPMENT STRATEGY FOR BUK DAR GROUND SPICE BUSINESS USING SOAR SAN QSPM METHOD - Fadhlan Fadhlan; Fitriani Surayya Lubis; Ismu Kusumanto; Suherman Suherman; Muhammad Nur (Jurnal Ekonomi, 2023)
UKM Bumbu Giling Buk Dar is one of the ground spice businesses that produces ready-to-use ground spices such as ground chili, dried ground chili, bird's eye chili, ground shallots, ground garlic, ground galangal, ground turmeric, ground lemongrass, ground ginger, and ground candlenut. Additionally, they also sell various other spices. Marketing for UKM Bumbu Giling Buk Dar is currently limited to the production site, stores, direct offers to the community, and regular customers from the food industry. The decline in UKM Bumbu Giling Buk Dar's sales can be attributed to several factors, including the COVID-19 pandemic, which has resulted in a decrease in consumer demand, as well as market competition and suboptimal promotion. To develop a marketing strategy, it is important to identify existing factors. This can be done using the SOAR method and identifying suitable alternative strategies using the QSPM matrix. A key opportunity for UKM Bumbu Giling Buk Dar lies in the development of the business world, enabling online sales platforms such as WhatsApp and others. The main outcome for UKM Bumbu Giling Buk Dar lies in expanding its marketing reach. Based on an IFE score of 4.604 and an EFE score of 4.109, the IE matrix places the company in Quadrant I, which represents intensive and integration strategies. Through the analysis of internal and external factors, several alternative strategies have been identified based on the SOAR matrix, including SA, OA, SR, and OR strategies. The marketing strategy to be employed, based on the QSPM method, is the SA strategy (utilizing strategic sales locations and expanding them through online media), with a TSS value of 8.533.